PATHOGENICITY OF HETERODERA SACCHARI (LUC AND MERNY) AND ITS INTERACTION WITH BOTRYODIPLODIA THEOBROMAE (PAT) ON SOME NERICA RICE CULTIVARS (2013)
The Cyst Nematode (CN), Heterodera sacchari, is an important pest that causes yield losses of upland rice. NERICA Rice (NR) is a widely-grown upland rice cultivar. Botryodiplodia theobromae (a rot fungus) exists in many agricultural lands and causes yield losses on crops. However, information on the pathogenicity and damage by CN on NR cultivars in Nigeria is scanty. Therefore, pathogenicity of CN on NR cultivars and its interaction with Botryodiplodia theobromae were investigated. Twenty-four upland cultivars were screened for resistance to H. sacchari by inoculating three-week old seedlings with zero and 5000 eggs of H. sacchari. Cyst rating following standard procedure was used to determine resistance/susceptibility. Pathogenicity of H. sacchari was conducted to determine nematode damage on NR1, NR2, NR3, NR8 and NR14 cultivars in pot and field experiments in two cropping seasons. Three-week old seedlings of each cultivar were inoculated in pot experiment at zero, 5000 and 10000 eggs of H. sacchari per pot in four replicates in a 5X3 factorial using Randomized Complete Block Design (RCBD). The field trial was a split-plot experimental design with nematode-treatment as main plot and the five NERICA rice cultivars as sub-plots. Interaction between H. sacchari and B. theobromae on NR was investigated in pot and microplot experiments using standard procedures. Three-week old seedlings of NR1 were inoculated at zero or 5000 eggs of H. sacchari alone, 5x105 spores ml-1 of B. theobromae alone and simultaneous inoculation of H. sacchari + B. theobromae per pot in four replicates in a RCBD. The same treatments were carried out for the seedlings in the microplots (50x50x75) cm. Plants were assessed for growth, yield and nematode-fungal damage. Root sections (14?m) of NR from the interaction experiment were prepared for histopathology studies using standard procedures. Photomicrographs of cell structural integrity and damage were taken. Data were analyzed using descriptive statistics and ANOVA at p=0.05. Twenty-one rice cultivars (seven improved Oryza sativa and 14 NR cultivars were rated susceptible), NR6 and NR8 were rated moderately resistant and CG14 was most resistant. Heterodera sacchari significantly reduced NR growth by 41.8%, root weight by 55.4% and yield by 67.7%. Interaction between H. sacchari and B. theobromae significantly reduced NR growth by 58.8% - 67.3%, root weight by 63.4% - 70.4% and yield by 62.2% - 75.4%, compared to single inoculation with H. sacchari or B. theobromae. Heterodera sacchari infection caused cellular disorganization, compression and disintegration. Syncytia with seven nuclei, were formed close to nematode head seven days after inoculation (DAI). Both CN and B. theobromae developed and reproduced when present on same root tissue. Fruiting bodies of B. theobromae enlarged and ruptured cortical cells and epidermal layer of root during ascospore discharge 7 DAI. Infection of both pathogens revealed dark necrotic regions, cellular compression, disorganization and disintegration. Syncytium was established by the nematode in presence of the fungus 9 DAI. Heterodera sacchari caused significant damage and yield reduction on NERICA Rice cultivars and its interaction with Botryodiplodia theobromae, synergistically reduced growth and yield of rice. However, CG14 was most resistant.